Single atomic Co coordinated with N in microporous carbon for oxygen reduction reaction obtained from Co/2-methylimidazole anchored to Y zeolite as a template. (June 2021) - Zhu, Y.; Miyake, K.; Shu, Y.; Moroto, K.; Hirota, Y.; Uchida, Y.; Tanaka, S.; Zheng, T.; Katayama, M.; Inada, Y.; Morallón, E.; Cazorla-Amorós, D.; et al.
Abstract: Zeolite-templated carbons (ZTCs) composed of curved and single-layer graphene frameworks have uniform micropores (ca. 1.2 nm) and high surface areas ( 4, 000 m 2 /g). Owing to their outstanding properties originating from the porous structures, ZTCs have been used in many applications. In this work, we synthesized Co/N-doped ZTC (Co/N-ZTC) by complexing Co ion with 2-methylimidazole in Y zeolite to expand further utilization of ZTCs. The obtained Co/N-ZTC has a high surface area (ca. 2, 000 m 2 /g) and single atomic Co species in CoNx moieties, which actually contributes to its excellent catalytic performance on oxygen reduction reaction. This synthetic concept is beneficial to fabricate single atomic transition metals coordinated with heteroatoms in ZTCs, which contributes to the progress of material design of single atomic catalyst–supported porous materials. Graphical abstract: Image 1 Highlights: tCo/N-doped zeolite-templated carbon (Co/N-ZTC) was fabricated using Co-2-methylimidazole anchored to zeolite Y as the template. The Co/N-ZTC showed excellent catalytic performance in oxygen reduction reaction. This work provides a new direction for the catalyst design of single atomic metal in uniform micropores of ZTCs.